Efectos de tratamientos fisionutricionales orgánicos y ecológicos sobre el rendimiento del plátano CV. barraganete - Almeida Cevallos, Antony Fabricio (2023)
The objective of the work was to evaluate the effectiveness of organic and ecological physionutritional treatments on the yield of plantain cv. Barraganete. The investigation was carried out from February 2022 to February 2023, at El Limón site in Bolívar canton. The treatments evaluated were soil organic-mineral amendments (T1), soil organic-mineral amendments + soil biostimulants (T2), soil organic-mineral amendments + soil and foliar biostimulants (T3), conventional chemical fertilization (T4) and control treatment (T5). A completely randomized block design (DBCA) was used, with five treatments, four repetitions and twenty experimental units. The main variables recorded were yields (t ha-1) and net economic benefit (USD ha-1). The yield was significantly affected (p<0.05) by the tested fertilization treatments, where the T3 and T4 treatments reached the highest yield with 12.43 and 13.01 (t ha-1), in relation to the other treatments that obtained less productivity. On the other hand, the highest net benefits of fertilization were achieved with the T2 and T4 treatments, with 1059 and 1355 USD ha-1, respectively. The results denote that, although organic fertilization is true, it does not achieve the agronomic yields of conventional chemical fertilization, the higher price offered for organic plantain financially compensates for the lower yield, so organic fertilization may be viable for plantain production.